Mutations in AIFM1 cause an X-linked childhood cerebellar ataxia partially responsive to riboflavin. (January 2018) - Heimer, G.; Eyal, E.; Zhu, X.; Ruzzo, E.K.; Marek-Yagel, D.; Sagiv, Doron; Anikster, Y.; Reznik-Wolf, H.; Pras, E.; Oz Levi, D.; Lancet, D.; Ben-Zeev, B.; et al.
Abstract: Background: AIFM1 encodes a mitochondrial flavoprotein with a dual role (NADH oxidoreductase and regulator of apoptosis), which uses riboflavin as a cofactor. Mutations in the X-linked AIFM1 were reported in relation to two main phenotypes: a severe infantile mitochondrial encephalomyopathy and an early-onset axonal sensorimotor neuropathy with hearing loss. In this paper we report two unrelated males harboring AIFM1 mutations (one of which is novel) who display distinct phenotypes including progressive ataxia which partially improved with riboflavin treatment. Methods: For both patients trio whole exome sequencing was performed. Validation and segregation were performed with Sanger sequencing. Following the diagnosis, patients were treated with up to 200 mg riboflavin/day for 12 months. Ataxia was assessed by the ICARS scale at baseline, and 6 and 12 months following treatment. Results: Patient 1 presented at the age of 5 years with auditory neuropathy, followed by progressive ataxia, vermian atrophy and axonal neuropathy. Patient 2 presented at the age of 4.5 years with severe limb and palatal myoclonus, followed by ataxia, cerebellar atrophy, ophthalmoplegia, sensorineural hearing loss, hyporeflexia and cardiomyopathy. Two deleterious missense mutations were found in the AIFM1 gene: p. Met340Thr mutation located in the FAD dependent oxidoreductase domain and the novel p. Thr141Ile mutation located in a highly conserved DNA binding motif. Ataxia score, decreased by 39% in patient 1 and 20% in patient 2 following 12 months of treatment. Conclusion: AIFM1 mutations cause childhood cerebellar ataxia, which may be partially treatable in some patients with high dose riboflavin. Highlights: AIFM1 encodes a mitochondrial NADH oxidoreductase and regulator of apoptosis, that uses riboflavin as a cofactor. Mutations in AIFM1 gene may cause ataxia, accompanied by axonal neuropathy and sensorineural hearing loss. Auditory neuropathy, a special type of sensorineural hearing loss, is characteristic for AIFM1 dysfunction. Severe myoclonus, presenting as status myoclonicus, should be added to the AIFM1 related ataxia phenotype. Treatment with riboflavin might be beneficial for improving ataxia score in these patients.